Global, regional, and national burden of low back pain in working-age population from 1990 to 2021 and projections for 2050 - Zhang, Cifeng; Lv, Bing; Yi, Qian; Qiu, Guicong; Wu, Fengling (Frontiers in Public Health, 2025)
BackgroundLow back pain (LBP) is a leading cause of disability worldwide, especially among working-age group. This study evaluates the global, regional, and national burden of LBP among individuals aged 15–64 utilizing data from the Global Burden of Disease (GBD) 2021 study.MethodsWe assessed trends in incidence, prevalence, and disability-adjusted life years (DALYs) for LBP from 1900 to 2021. Age-standardized rates (ASRs) were calculated, and joinpoint regression and decomposition analyses were used to identify key drivers. Future trends were projected through 2050.ResultsThe prevalence of LBP in working-age group has risen to 452.8 million cases globally, a 52.66% increase since 1990. South Asia reported the highest absolute number of cases, while Central and Eastern Europe showed the highest ASRs. Across all regions, women consistently exhibited higher incidence, prevalence, and DALYs than men. Decomposition analysis revealed that population growth was the main factor contributing to the rising burden. Projections indicate that LBP cases will continue increasing through 2050, particularly among women, although ASRs are expected to decline.ConclusionThe burden of LBP among working-age group is growing due to population expansion. Despite declining ASRs, substantial regional and gender disparities remain, highlighting the need for targeted public health strategies.